Activation of Nrf2 decreases bile acid concentrations in livers of female mice. (4th May 2021) - Liu, Jing; Lickteig, Andrew J.; Zhang, Youcai; Csanaky, Iván L.; Klaassen, Curtis D.
Abstract: 1. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a master regulator of oxidative/electrophilic stress. Studies suggest a role of Nrf2 in regulating bile acid (BA) metabolism in male mice. However, whether Nrf2 is important for BA homeostasis in female mice remains undefined. In this study, we systematically investigated the effect of Nrf2 activation, either through CDDO-imidazolide (CDDO-Im) treatment or genetic modulation of Kelch-like ECH associating protein 1 (Keap1), on BA homeostasis in female mice. 2. Both pharmacological and genetic Nrf2 activation increased mRNA levels of multidrug resistance‐associated protein 2 and 3 (Mrp2 and Mrp3), two Nrf2 target genes, in livers and ilea of female mice. Both pharmacological and genetic activation of Nrf2 decreased BA concentrations in the liver, which did not appear to be due to increased biliary BA excretion or decreased ileal BA absorption. Importantly, both pharmacological and genetic activation of Nrf2 downregulated hepatic Cyp7a1 mRNA, which might be attributable to the upregulation of the Fxr-Fgf15 signalling in the ileum. 3. To conclude, Nrf2 activation lowers BA concentrations in livers of female mice, which appears to be attributable to the decreased hepatic BA synthesis.